Concepts, features and types of administrative procedures (Law and Safety, 2020)
Administrative procedures that are in force in Ukraine have been analyzed; their concepts, features and types have been defined. It has been indicated that understanding the content and essence of administrative procedures is a kind of success in qualitative cognition of the entire system of administrative law.The semantics of the term of “administrative procedure” has been specified. It has been offered to understand it as the procedure of administrative proceedings determined by the current legislation of Ukraine.Administrative and judicial, management procedures have been characterized. It has been emphasized that administrative procedures by their functional purpose are inextricably linked with management activities, as well as with the exercise of power.The classification of administrative procedures by their nature, types and purpose has been offered.It has been noted that clearly defined administrative procedures will greatly help the government in establishing a regime of maximum assistance to government agencies and public associations. In this way, the government will be able to ensure the maintenance of the rule of law in Ukraine, which inevitably leads to increased efficiency of the entire state system. It has been stated that the norms that determine administrative procedures should become a reliable foundation for the positive legal activity of the subjects of power.The author has substantiated the conclusion that if the authorities comply with certain requirements for the content and form of administrative procedures (their clarity, unambiguity and focus on effective protection of human and civil rights, freedoms and interests), the possibility of introducing such a management and decision-making system there will be arbitrariness, corruption or inefficiency. To some extent, such actions will also contribute to the establishment of better interaction both between government agencies and between government and citizens.The author has provided recommendations, with the help of which it is possible to bring the functional purpose of administrative procedures to a fundamentally new level. It is also important to consider the current administrative procedures through the prism of their effectiveness in the changing realities of reforming national legislation.
Keywords: an administrative procedure; administrative activity; administrative law; a structure; a system; administrative proceedings; legal regulation; administrative process